2015
DOI: 10.1186/s13068-015-0333-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of Zymomonas mobilis ZM4 reveals mechanisms of tolerance and detoxification of phenolic aldehyde inhibitors from lignocellulose pretreatment

Abstract: BackgroundPhenolic aldehydes generated from lignocellulose pretreatment exhibited severe toxic inhibitions on microbial growth and fermentation. Numerous tolerance studies against furfural, 5-hydroxymethyl-2-furaldehyde (HMF), acetate, and ethanol were reported, but studies on inhibition of phenolic aldehyde inhibitors are rare. For ethanologenic strains, Zymomonas mobilis ZM4 is high in ethanol productivity and genetic manipulation feasibility, but sensitive to phenolic aldehyde inhibitors. Molecular mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 30 publications
3
82
1
Order By: Relevance
“…Furthermore, combinations of HMF, furfural, and acetate resulted in additive rather than synergistic inhibition to Z. mobilis cell growth (Franden et al 2013). It was also observed that Z. mobilis is capable of converting aldehydes of furfural, HMF, vanillin, 4-hydroxybenzaldehyde, and syringaldehyde to their corresponding alcohol forms of furfuryl, 5-hydroxymethylfurfural, vanillyl, 4-hydroxybenzyl, and syringyl alcohol, respectively (Franden et al 2013;Yi et al 2015). These studies suggested that the enhanced conversion of toxic aldehydes into the relatively benign alcohol forms with engineered strains could reduce process cost by improving ethanol yields and/or by reducing fermentation time.…”
Section: Evaluation Of the Effect Of Hydrolysate Inhibitors On Z Mobmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, combinations of HMF, furfural, and acetate resulted in additive rather than synergistic inhibition to Z. mobilis cell growth (Franden et al 2013). It was also observed that Z. mobilis is capable of converting aldehydes of furfural, HMF, vanillin, 4-hydroxybenzaldehyde, and syringaldehyde to their corresponding alcohol forms of furfuryl, 5-hydroxymethylfurfural, vanillyl, 4-hydroxybenzyl, and syringyl alcohol, respectively (Franden et al 2013;Yi et al 2015). These studies suggested that the enhanced conversion of toxic aldehydes into the relatively benign alcohol forms with engineered strains could reduce process cost by improving ethanol yields and/or by reducing fermentation time.…”
Section: Evaluation Of the Effect Of Hydrolysate Inhibitors On Z Mobmentioning
confidence: 99%
“…Using conventional and high-throughput growth assays, effects of inhibitory hydrolysate compounds on Z. mobilis growth and fermentation have been investigated (Dong et al 2013;Franden et al 2009Franden et al , 2013Gu et al 2015;Yi et al 2015). The results demonstrated that acetate, furfural, and phenolic aldehydes are three major inhibitors in the dilute acid-pretreated corn stover hydrolysate for Z. mobilis, and the inhibitory activity was strongly correlated to the hydrophobicity of these compounds.…”
Section: Evaluation Of the Effect Of Hydrolysate Inhibitors On Z Mobmentioning
confidence: 99%
See 2 more Smart Citations
“…"Z. mobilis cellulase," BioResources 12(1), 1165-1178. 1166 production of byproducts, lower biomass production, no requirement for controlled addition of oxygen during fermentation, and tolerance to toxic inhibitors and substrates (Rogers et al 2007;Yang et al 2014;Gu et al 2015;Yi et al, 2015). These characteristics make Z. mobilis a promising ethanologenic microorganism for large-scale production of bioethanol from sugar rich substrates or lignocellulosic materials; the technology can be further developed to provide a CBP microbe in the ethanol production using lignocellulosic material (Sarks et al 2016).…”
Section: Introductionmentioning
confidence: 99%